2018
DOI: 10.2147/ndt.s176047
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the relationships among neurosteroid serum levels, cognitive function, and quality of life

Abstract: BackgroundDehydroepiandrosterone (DHEA), its sulfate ester (DHEA-S), and pregnenolone are neurosteroids that can be synthesized in the brain. Previous studies have hypothesized that these neurosteroids have antiaging, mood-enhancing, and cognitive-preserving effects; however, these effects may be gender-specific. Therefore, the purpose of this study was to investigate the gender differences in the relationships among neurosteroids (DHEA, DHEA-S, and pregnenolone), cognitive function, and quality of life in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The neuroprotection provided by exogenous administration of these hormones extends to males as well. However, it is evident ( Chen et al, 2018 ) that the efficacy of neurosteorids for cognitive function may differ between the genders. Moreover, neurosteroids may be involved in the gender differences found in the susceptibility to schizophrenia ( Huang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotection provided by exogenous administration of these hormones extends to males as well. However, it is evident ( Chen et al, 2018 ) that the efficacy of neurosteorids for cognitive function may differ between the genders. Moreover, neurosteroids may be involved in the gender differences found in the susceptibility to schizophrenia ( Huang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings in healthy subjects underlined the higher impact of NAS on cognition in men than in women (59). For example, the role of testosterone in cognitive impairment has been discussed in male patients with schizophrenia only (37).…”
Section: Discussionmentioning
confidence: 93%
“…A large-scale cohort study in the U.S. suggested that women may have greater cognitive reserve but faster cognitive decline than men, which may contribute to sex differences in late-life dementia [10]. Our previous study, it demonstrated that the correlation between neurosteroids and cognitive function and psychological well-being may differ with sex [11]. Therefore, the uncertain mechanisms of the sexspecific effect on cognition and quality of life warrant further clarification.…”
Section: Introductionmentioning
confidence: 94%